(untitled) (Studia Prawnicze / The Legal Studies, 1991)
Art. 60 § 2 k.r.o. umożliwia rozstrzyganie innych [niż alimenty] nowo powstałych w wyniku rozwodu sytuacji społecznych, przede wszystkim tych stanów faktycznych, które dotyczą obojga pracujących zawodowo rozwiedzionych małżonków. Wiele bowiem kobiet pracuje intensywnie zawodowo zarówno przed, jak i po rozwodzie, jednak konieczność samodzielnej egzystencji wraz z dziećmi powoduje często bardzo znaczne obniżenie poziomu życia takiej rodziny niepełnej, aczkolwiek jeszcze powyżej poziomu niedostatku, co uniemożliwia zastosowanie przepisu art. 60 § 1 k.r.o. Uzasadnione jest także stosowanie przepisu art. 60 § 2 k.r.o. jako podstawy prawnej alimentacji na rzecz rozwiedzionych ojców samotnie wychowujących dzieci, zwłaszcza - co zdarza się już obecnie - gdy w chwili rozwodu przebywają oni na urlopie wychowawczym. Przesłanka przyczynienia się do rozkładu pożycia (winy) występuje w różnych postaciach w treści całej instytucji obowiązku alimentacyjnego między rozwiedzionymi małżonkami. Rozwód w każdym przypadku ogranicza zakres obowiązku alimentacyjnego w porównaniu z zakresem obowiązku z art. 27 k.r.o. Stopień tego ograniczenia zależy jednak w każdym przypadku od tego, czy strony przyczyniły się do rozkładu pożycia. Jeżeli strony nie przyczyniły się do rozkładu pożycia albo przyczyniły się w równym stopniu, to ich obowiązek alimentacyjny po rozwodzie zredukowany będzie tak dalece, iż wystąpi tylko w rzadkim obecnie przypadku niedostatku po stronie jednego z byłych małżonków. Gdy natomiast tylko jedna ze stron wyłącznie przyczyniła się do rozkładu pożycia, a nadto rozwód spowodował istotne pogorszenie sytuacji materialnej drugiego małżonka, ograniczenie zakresu obowiązku alimentacyjnego po rozwodzie będzie mniejsze. O tym, czy obowiązek alimentacyjny będzie trwał po rozwodzie w mniej lub więcej ograniczonym zakresie, nie decyduje tylko wina zobowiązanego; art. 60 § 2 k.r.o. zawiera bowiem podwójną przesłankę: winy i skutku rozwodu, jakim jest istotne pogorszenie. Samo stwierdzenie wyłącznej winy nie wpływa na zakres ograniczenia więzi alimentacyjnej między rozwiedzionymi małżonkami. Rozważając "szerszy" obowiązek alimentacyjny nie należy rozwodzić się nad wyłączną winą zobowiązanego, ale rozważyć, czy wykazał w niezbędnym stopniu zainteresowanie losem współmałżonka. Nadmierne akcentowanie przesłanki winy i wprowadzenie odszkodowawczych treści do omawianego obowiązku uznać można nie tylko za swoiste "tworzenie bytów ponad potrzebę", ale nadto takie podejście odwróci uwagę od dużo ważniejszego zagadnienia - zapewnienia godziwego poziomu egzystencji opuszczonemu małżonkowi. Doszukiwanie się odszkodowawczych elementów w obowiązku [o którym mowa w art. 60 § 2 k.r.o.] nie jest dopuszczalne w świetle ugruntowanego w prawie cywilnym znaczenia pojęcia odpowiedzialności odszkodowawczej. Nie sposób przyjąć, że strona dążąca do rozwodu, a więc działająca w ramach swojego prawnie chronionego interesu mogłaby narazić się na odpowiedzialność odszkodowawczą, chyba że owa odpowiedzialność miałaby inny niż ustalany w prawie cywilnym charakter. Rozpatrując z aksjologicznego punktu widzenia zakres całej instytucji obowiązku alimentacyjnego z art. 60 k.r.o. i biorąc pod uwagę treść obowiązku z art. 27 k.r.o., uważam za słuszne, iż ten ostatni obowiązek ma zdecydowanie najszerszy zakres - dotyczy przecież małżonków. Z kolei obowiązek względem byłego małżonka, który w równym stopniu przyczynił się do zaistniałej (w wyniku rozwodu) zmiany swojej sytuacji ekonomicznej, ma najwęższy zakres, zapobiegając tylko niedostatkowi. I wreszcie trafnie w sposób pośredni ujęto zakres obowiązku alimentacyjnego względem tego małżonka, który nie przyczynił się do rozkładu pożycia, spowodowanego wyłącznie przez drugą stronę. Zwracając większą uwagę na strukturalnie ujmowane ekonomiczne konsekwencje rozwodu, opowiedzieć się należy za szerszym stosowaniem przepisu art. 60 § 2 k.r.o. w sposób uwzględniający istotne zmiany sytuacji społecznej, jakie dokonują się w grupie rozwiedzionych małżonków. Article 60(2) of the Family and Guardianship Code enables decision-making related to other [than maintenance payments] social situations resulting from a divorce, mainly in those actual situations which apply to both professionally active, divorced spouses. Indeed, many women work intensively both before and after the divorce, but the necessary, independent live with the children often results in a very significant reduction in the standard of living of such a single-parent family, albeit it still remains above the level of deprivation, which prevents the application of the provision of Article 60(1) of the Family and Guardianship Code. It is also justified to use the provision of Article 60(2) of the Family and Guardianship Code as a legal basis for alimony in favour of divorced single fathers, especially - as already happens today - when they are on a parental leave at the time of divorce. The condition of contributing to the decomposition of co-habituation (fault) is present in various forms in the scope of the entire maintenance obligation institution existing between the divorced spouse. In any case, a divorce limits the scope of a maintenance payment obligation compared to the scope of the obligation resulting from Article 27 of the Family and Guardianship Code. However, the extent of this limitation depends in each case on whether the parties contributed to the marriage breakdown. If the parties did not contribute to the marriage breakdown or their contribution was equal, their maintenance obligation after the divorce will be reduced to such an extent that it will only be present in the now rare case of deprivation experienced by of one of the former spouses. When, on the other hand, only one of the parties has exclusively contributed to the marriage breakdown and the divorce has also caused a significant deterioration in the financial situation of the other spouse, the reduction in the extent of the maintenance obligation after divorce will be smaller. Whether the maintenance obligation will remain in force after the divorce to a more or less limited extent is not determined solely by the fault of the obliged party; indeed, Article 60(2) of the Family and Guardianship Code contains a double condition: of the fault and the consequence of the divorce, namely a substantial deterioration of the situation. The conclusion of an exclusive fault alone does not impact the extent, to which the maintenance relation between the divorced spouses is limited. When considering the “wider” maintenance obligation, it is not necessary to dwell on the exclusive fault of the obliged party, but to consider whether he or she has shown the necessary degree of interest in the fate of his or her spouse. The excessive emphasis on the circumstance of fault and introduction of compensatory topics to the discussed obligation may be deemed not only as a peculiar “creation of unnecessary items”, but such an approach also diverts attention from a much more important issue - ensuring an adequate standard of living for the divorced spouse. The search for compensatory elements in the obligation [referred to in Article 60(2) of the Family and Guardianship Code] is not permissible in the light of the meaning of the concept of compensatory liability well-established in civil law. It is impossible to assume that a party seeking a divorce and thus acting within the framework of his or her legally protected interest could expose himself or herself to liability for damages, unless this liability were of a different nature than that established under civil law. Considering the scope of the entire maintenance obligation institution dictated by Article 60 of the Family and Guardianship Code from the axiological point of view and taking into account the contents of the obligation dictated by Article 27 of the Family and Guardianship Code, I think it is right that the latter obligation has the widest scope - as it is related to the spouses. On the other hand, the obligation towards a former spouse who equally contributed to the current (caused by the divorce) change of his or her economic situation has the most narrow scope, preventing only destitution. Lastly, the scope of the maintenance obligation towards the spouse who did not contribute to the marriage breakdown, which was caused solely by the other party, is correctly addressed in an indirect manner. Paying more attention to the structurally approached economic consequences of divorce, one should advocate for a wider application of the regulation of Article 60(2) of the Family and Guardianship Code in a manner taking into account significant changes to the social situation which take place in the group of divorced spouses.